OVERVIEW OF PUBLIC KNOWLEDGE AND ATTITUDE TOWARDS HEALTH IMPACT POST FLOOD DISASTER IN ENVIRONMENT V, KAYUBULAN VILLAGE, GORONTALO REGENCY - Hasan, Zahwanabila Ramadhanti; Suleman, Ibrahim; Rahma, Sitti; Yusuf, Zuhriana K; Pomalango, Zulkifli B (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
After floods submerge residential areas, various diseases often appear. Diseases that arise due to flooding, such as ISPA, diarrhea, skin infections, leptospirosis, and fever. Lack of knowledge and attitudes about public health education is one of the causes of disease. So this research aims to determine the level of knowledge and attitudes of the community regarding the health impacts caused. This research method is a descriptive survey research design with a quantitative approach to determine the level of knowledge and attitudes. The population in this research is each community's family card. The sampling method in this research was purposive sampling with the Slovin formula 0.1. The results of this research show that 67 people (91.8%) have a good level of knowledge and 6 people (8.2%) have a good level of knowledge. The research results for attitude show that 71 people (97.3%) have a good attitude and 2 people (2.7%) have an adequate attitude. The results of this research can be a reference for the public to maintain personal health and hygiene.